Minocycline partially reverses established PTSD-related behavioral traits in rats exposed to repetitive low-level blast injury - Pérez Garcia, Georgina; Perez, Gissel M.; De Gasperi, Rita; Gama Sosa, Miguel A.; Abutarboush, Rania; Kawoos, Usmah; Zhu, Carolyn; Toro, Carlos A.; Hof, Patrick R.; Ahlers, Stephen T.; Elder, Gregory A. (Frontiers in Neurology, 2025)
IntroductionMany military Veterans who experienced blast-related traumatic brain injuries (TBI) in the conflicts in Iraq and Afghanistan currently suffer from chronic cognitive and mental health problems including post-traumatic stress disorder (PTSD). Rats exposed to repetitive low level blast injury exhibit chronic PTSD-related behavioral traits. Inflammation has long been suspected of playing a role in blast-induced brain injury and rats exposed to repetitive low-level blast develop chronic inflammatory changes. Minocycline is a tetracycline antibiotic that besides having antibacterial properties has anti-inflammatory activity. The aim of this study was to determine whether minocycline could reverse PTSD related behavioral traits in rats exposed to repetitive low level blast exposure.MethodsRats were exposed to three 74.5 kPa blast exposures administered one per day for three consecutive days. We tested two cohorts of blast-exposed rats at 8–8.5 months after blast exposure. Rats were tested in a novel object recognition (NOR) task, elevated zero maze (EZM) and cued fear learning paradigm. In one experiment rats were treated with five doses of minocycline over a 9-day period. In the second experiment blast-exposed rats were treated with a 4-week course of minocycline with the drug administered 11 times. After the second experiment blast-induced effects on expression of the serotonin receptor 2A (5-HT2AR) and the post-synaptic density protein-95 (PSD-95) were examined by Western blotting. Microglial morphology was examined by Iba1 immunostaining.ResultsIn both experiments, cognitive changes in NOR and anxiety in an EZM were reversed by minocycline. However, in neither experiment was exaggerated fear learning rescued. Minocycline did not reverse blast induced effects on expression of 5-HT2AR or PSD-95 although it did appear to modulate blast-induced effects on microglial morphology.ConclusionsThese studies have implications for understanding the nature of blast-induced behavioral traits, some of which may be the direct result of inflammatory effects, while others may be independent of inflammation or if the result of inflammation, not reversible once downstream structural or neurochemical changes are established.